210k views
2 votes
-3 (k+7)-5k+4=23 what is k

2 Answers

5 votes

Answer:


k = - 5

Explanation:

Step 1: Simplify both sides of the equation.


−3(k+7)−5k+4=23 \\ (−3)(k)+(−3)(7)+−5k+4=23(Distribute) \\−3k+−21+−5k+4=23 \\ (−3k+−5k)+(−21+4)=23(Combine Like Terms) \\ −8k+−17=23 \\ −8k−17=23

Step 2: Add 17 to both sides.


−8k−17+17=23+17 \\ −8k=40

Step 3: Divide both sides by -8.


( - 8k)/( - 8)= (40)/( - 8)


k = - 5

User Matt Casto
by
5.0k points
3 votes
hope this helps! feel free to clarify
User Jpsmith
by
5.2k points